Hexakis(1H-imidazole-κN (3))nickel(II) bis(2,4-dibromo-6-formylphenolate) N,N-dimethylformamide disolvate - Ding, Yu (International Union of Crystallography, 2008)
In the cation of the title compound, [Ni(C(3)H(4)N(2))(6)](C(7)H(3)Br(2)O(2))(2)·2C(3)H(7)NO, the Ni(II) ion lies on an inversion center and is coordinated in a slightly distorted octahedral environment by six N atoms from six imidazole ligands. In the crystal structure, cations, anions and solvent molecules are linked by intermolecular N—H⋯O hydrogen bonds into one-dimensional chains along [010]. In addition, the crystal structure is stabilized by weak C—H⋯O and C—H⋯N hydrogen bonds.